HIV care continuum characteristics among people with opioid use disorder and HIV in Vietnam: baseline results from the BRAVO study - Caroline King; Le Minh Giang; Gavin Bart; Lynn Kunkel; P. Todd Korthuis (BMC, 2020)
Abstract Background Little is known about patient characteristics that contribute to initiating antiretroviral therapy (ART) and achieving viral suppression among HIV people with opioid use disorder in Vietnam. The primary objective of this analysis was to evaluate associations between participant characteristics and the critical steps in the HIV care continuum of ART initiation and HIV viral suppression among people with opioid use disorder and HIV in Vietnam. Methods We assessed baseline participant characteristics, ART status, and HIV viral suppression (HIV RNA PCR < 200 copies/mL) enrolled in a clinical trial of HIV clinic-based buprenorphine versus referral for methadone among people with opioid use disorder in Vietnam. We developed logistic regression models to identify characteristics associated with ART status and HIV viral suppression. Results Among 283 study participants, 191 (67.5%) were prescribed ART at baseline, and 168 of those on ART (90%) were virally suppressed. Years since HIV diagnosis (aOR = 1.12, 95% CI 1.06, 1.19) and being married (aOR = 2.83, 95% CI 1.51, 5.34) were associated with an increased likelihood of current prescription for ART at baseline. Greater depression symptoms were negatively associated with receipt of ART (aOR = 0.97, 95% CI = (0.94, 0.9963)). In the HIV suppression model, once adjusting for all included covariates, only receipt of ART was associated with viral suppression (aOR = 25.9, 95% CI = (12.5, 53.8). In bivariate analyses, methamphetamine was negatively correlated with ART prescription (p = 0.07) and viral suppression (p = 0.08). Conclusion While fewer than 90% of participants had received ART, 90% of those on ART had achieved HIV viral suppression at baseline, suggesting that interventions to improve uptake of ART in Vietnam are essential for achieving UNAIDS 90-90-90 goals in people who use heroin in Vietnam. Social determinants of health associated with ART and HIV viral suppression suggest that social support may be a key to facilitating both of these steps in the HIV care continuum.